STUDI KASUS RENDAHNYA MOTIVASI MELANJUTKAN STUDI LULUSAN SMP DI KELURAHAN GIRIWUNGU KECAMATAN PANGGANG GUNUNGKIDUL - Oktaviani, Anita (Fakultas Psikologi Universitas Ahmad Dahlan Yogyakarta, 2012)
AbstractThis research has the aim to find the data about the causes of low motivationof the graders of junior high school in Giriwungu village, Panggang district,Gunungkidul to continue their study. The subject of this research is three teenswho do not continue their study. The subjects live in Giriwungu village, Panggangdistrict, Gunungkidul. The ages of the subjects are about 16-22 years old. Theresearch method that is used is qualitative research using phenomenologyresearch. The data collecting method are using semi structured interview andnon participant observation. The result of the research shows that the lowmotivation to continue study of the Junior High School graders in Giriwungu village, Panggang district, Gunungkidul caused by trauma in school because ofthe problem of getting punishment and facing an unkind teacher so that they aredifficult to understand the lesson. Majority, friends who do not study in schoolmake the subjects think that school is not important because without schoolthey can work. Also parents do not give more attention and suggestion aboutthe important of formal school. Besides the researcher also finds another activitythat is done after stopping study; they can play with their friend anytime whilehelping their parents and working with less ability or less knowledge.Keywords: low motivation to continue study, and junior high school student.